Exploring the association between dietary vitamin A and coronary artery disease risk in men and women: findings from a US population study - Wu, Zhijian; Yang, Weichang; Fang, Haiyang; Chen, Yi; Wu, Yanqing; Gong, Ren (Frontiers in Nutrition, 2024)
Coronary artery disease (CAD) is an important public health problem with negative impacts on individual health and socioeconomics. Studies on the relationship of dietary vitamin A (DVA) to CAD are limited and conflicting. The purpose of this study was to investigate the relationship between DVA and the prevalence of CAD in U.S. adults, with particular interest in sex differences. Data from 26,449 NHANES participants were used for analysis. The association of DVA with the prevalence of CAD was investigated utilizing multivariate logistic regression models and fitted smoothed curves, and interaction tests were performed to explore potential modifiers. This study included 12748 males and 13701 females aged 50.34 ± 17.54 years. Overall, adjusted DVA was linearly negatively correlated with CAD (per natural ln (DVA) increment: OR 0.91, 95%CI 0.83-0.99). Multivariate regression analysis showed that among female participants, each natural increment of ln DVA was associated with a 22% reduction in CAD prevalence (OR 0.78, 95% CI 0.68-0.89). However, there was no significant correlation in male participants (P for interaction <0.001). DVA was negatively associated with the prevalence of CAD, and further analysis revealed an interaction between DVA and sex in terms of CAD prevalence.